Women in leadership : contextual dynamics and boundaries - Klenke, Karin (Emerald Publishing Limited, 2017)
Women leaders in many parts of the world have leadership opportunities that never existed before as a result of technology, globalization, and demographic shifts that have produced more female graduates than in the past and created a workforce which consists almost 50% of women. Ever more so, in today's rapidly changing environment, the contexts in which women exercise leadership is critically important in shaping their leadership style. At the same time, objectifying women in contexts such as sports and the media or the patriarchal ideology that permeates contexts such as the military and the church have changed very little. This book, updated and expanded from the 2011 first edition, acknowledges and discusses the belief that the context in which women exercise leadership is critically important in shaping their leadership style. Each chapter opens with a vignette of an extraordinary leader in the respective context, presents a contextual analysis, and discusses issues, controversies and paradoxes germane to the context of interest. What is the future of women's leadership in a global environment characterized by ambiguity, uncertainty, increasing interdependence and interconnectivity? Award-winning author Karin Klenke shows us in this revised edition of Women in Leadership.
Includes index.
Keywords: Leadership in women.; Business & Economics -- Leadership.; Organizational theory & behaviour.; elektronické knihy; electronic books